2016
DOI: 10.1136/bjophthalmol-2016-308658
|View full text |Cite
|
Sign up to set email alerts
|

Optimising keratoplasty for Peters' anomaly in infants using spectral-domain optical coherence tomography

Abstract: Our study showed that information gained from OCT under anaesthesia allows surgeons to classify type and severity of Peters' anomaly and supports surgical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Dabei konnte vor allen Dingen die Peter-Anomalie als Differenzialdiagnose einer bspw. kongenitalen endothelialen Hornhautdystrophie ausgeschlossen werden [12,34]. Auch bei der anschließenden Behandlung, bspw.…”
Section: Die Intraoperative Oct Bei Der Behandlung Von Endothelialen unclassified
“…Dabei konnte vor allen Dingen die Peter-Anomalie als Differenzialdiagnose einer bspw. kongenitalen endothelialen Hornhautdystrophie ausgeschlossen werden [12,34]. Auch bei der anschließenden Behandlung, bspw.…”
Section: Die Intraoperative Oct Bei Der Behandlung Von Endothelialen unclassified
“…As a fast, high-resolution, and noninvasive imaging technique, anterior segment optical coherence tomography (OCT) has proven to be valuable in pre-and intra-operative examinations of children with congenital corneal opacities. [7][8][9] The information obtained in this way could be useful in clarifying diagnoses, categorizing Peters' anomaly and guiding surgical intervention. [7][8][9] The purpose of this study was to evaluate the corneal grafts and AS after PK in patients with Peters' anomaly using anterior segment OCT.…”
Section: Introductionmentioning
confidence: 99%
“…Since the light of visible wavelengths of slit lamp biomicroscope is scattered by the corneal edema as in this case, an infrared anterior segment camera employing light of longer wavelengths could be used instead to clearly observe the corneal lesion and to reveal the spatial relation between the cornea and the iris [ 8 ]. To confirm the posterior corneal defects which is the essential feature of Peters’ anomaly, however, high-resolution and noninvasive imaging techniques such as ultrasound biomicroscopy (UBM) and optical coherence tomography (OCT) would be of greater value to clinicians [ 4 , 9 , 12 ]. Although both techniques were demonstrated to be effective in diagnosis of Peters’ anomaly, OCT was suggested to produce more accurate and clear images of the anterior segment compared with UBM [ 12 ].…”
mentioning
confidence: 99%
“…One of those cats underwent phacoemulsification for lens removal and a corneal graft surgery using a porcine small intestinal submucosa biomaterial to repair the cornea [ 6 ]. In humans, it was demonstrated that anatomical information gained from OCT could support surgical decision making in patients ahead of penetrating keratoplasty, for example finding a safe corneal penetration site and hence avoiding possible iris injury and preventing unnecessary cataract/glaucoma surgery [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation